2015
DOI: 10.1016/j.foodres.2015.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of traditional Macedonian edible oils by their fatty acid composition and their volatile compounds

Abstract: The fatty acid composition and volatile compounds of selected traditional Macedonian edible oils of several varieties, including sunflower seeds, pumpkin seeds, flax seed, rapeseed and sesame seeds, were analysed. The fatty acid (FA) composition was determined by GC-FID analysis after transesterification into the corresponding methyl esters. α-Linolenic acid (C18:3) was the main unsaturated fatty acid in flax seed oil (56.2% of total FA), oleic acid (C18:1) dominated in rapeseed and sesame seed oils (65.3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 36 publications
4
55
0
7
Order By: Relevance
“…Poyato et al reported that aldehydes are formed during edible oil degradation even at temperatures as low as 180 °C, and the amount of aldehydes increase with temperature and time. Ivanova‐Petropulos et al further confirmed that the exact composition of aldehydes in edible oils includes alkanals, alkenals and alkadienals. Our results show that the increase in absorption at 1714 cm −1 in trilinolein and trilinoelaidin is not obvious at 180 and 240 °C (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Poyato et al reported that aldehydes are formed during edible oil degradation even at temperatures as low as 180 °C, and the amount of aldehydes increase with temperature and time. Ivanova‐Petropulos et al further confirmed that the exact composition of aldehydes in edible oils includes alkanals, alkenals and alkadienals. Our results show that the increase in absorption at 1714 cm −1 in trilinolein and trilinoelaidin is not obvious at 180 and 240 °C (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Further, phytochemicals are reported to act as pro‐oxidants at very high concentrations, which can explain the different VOC profiles of sage and thyme flavored oils. Previous studies performed on edible oils correlated the presence of C6 aldehydes such as hexanal with green, apple, or grass aroma . Within the group of alcohols, sage was the only flavored oil to lack of hexanol, which was a major compounds of the other oils.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise to H‐U, α ‐pinene was the main terpene, representing ∼41% of the total amount, followed by β ‐pinene, limonene, 3‐carene, trans ‐ β ‐ocimene, as well as linalool. The last compound has been identified as dominant in SS oil . Furthermore, nine carbonyl compounds (e.g., hexanal, nonanal, heptanal, 4‐methyl‐2‐hexanone, etc.…”
Section: Resultsmentioning
confidence: 99%